Tinjauan Teologis Konsep Keselamatan Menurut Roma 10:9 dan Implikasinya Bagi Penginjilan Masa Kini - Paulus Kunto Baskoro (Jurnal Teologi (JUTEOLOG), 2021)
Safety is fundamental part of human life. The issue of the doctrine of salvation is a never-ending discussion. Because this is closely related to a belief in life in the future. Yet not many people take seriously the importance of salvation. There are some people who say salvation is matter of later, what important now is to focus on life in this wolrd. So it very necessary for every believer to take responsibility for preaching the gospel of salvation. Because of what is happening now, many believers are more focused on living tn the present. Many believres do not take their evangelistic mandate seriously and consistenly, even though the content of salvation is extraordinary and veru clear. As a believer, preaching the gospel is a task that is most basic and even become a believer’s lifestyle. Because salvation in Jesus is an important principle whose end is eternal salvation. The context of this discussion is focused on the theological overview of the concept of through writing, namely, First, believers understand how important the meaning of salvation is for everyone. Second, belivers fulfill the call to carry out the great commission in all aspects of life; Third, every believer always has creativity in conveying the gospel message to everyone who does not believe in Jesus.